Bioadhesive polymeric nanoparticles as strategy to improve the treatment of yeast infections in oral cavity: in-vitro and ex-vivo studies. (July 2018) - Roque, Luís; Castro, Pedro; Molpeceres, Jesús; Viana, Ana S.; Roberto, Amílcar; Reis, Cláudia; Rijo, Patrícia; Tho, Ingunn; Sarmento, Bruno; Reis, Catarina
Graphical abstract: Highlights: Different polymeric nanoparticles were compared in terms of their stability, size and surface charge. Preparations of semi-solid formulations were described. Polymeric nanoparticles increased the absorption and they prolonged the activity of the encapsulated drug (Nystatin). Abstract: Candidiasis is by far the most common fungal infection in the oral cavity and locally antifungal drugs are generally considered the first line therapy. However, some antifungal drugs like Nystatin (Nys) have very short time in the target tissue, which generally it requires several daily applications. One of the solutions to overcome those issues could be the incorporation of Nys into small, protective and polymeric nanoparticles (NPs). In this work, unloaded NPs were prepared and fully characterized and implemented in toothpaste and an oral gel. The three-best unloaded system (smallest, stable, safe and bioadhesive) was selected for further studies. After loading, NPs presented a size range from 300 to 800 nm, high encapsulation efficiency (above 70%), prolonged release and high adhesion capacity to oral mucosa when compared with free Nys. Free Nys lost its activity when it was not encapsulated. The presented results suggested that these new bioadhesive systems could be considered as good candidates to improve the time residence of Nys in buccal mucosa, reducing the number of applications during the day, using alcohol free-formulations and easily included in the daily lives of the patients.